Das etwas andere Subjekt: der blinde Fleck der Postmoderne - Müller, Klaus (Zeitschrift für katholische Theologie, 1998)
Though postmodern ideas are now being widely accepted within Catholic theology, new discussions are beginning regarding subjectivity. Nietzsche and Heidegger may have deconstructed many Enlightenment myths, but there are also indications that the individual subject may be ripe for rehabilitation. The present article explores some of these indications. A retrieved philosophical concept of subjectivity is a resource of fundamental importance for any responsible and critical theology in the postmodern era.